Autologous transplantation of the retinal pigment epithelium and choroid in the treatment of neovascular age-related macular degeneration. - Maclaren, R; Uppal, G; Balaggan, K; Tufail, A; Munro, P; Milliken, AB; Ali, R; Rubin, G; Aylward, G; da Cruz, L (2007)
PURPOSE: To assess excision of choroidal new vessels (CNV) combined with autologous transplantation of the equatorial retinal pigment epithelium (RPE) as a means of restoring vision for patients with acute neovascular age-related macular degeneration (AMD). DESIGN: Prospective interventional cohort study. PARTICIPANTS: Twelve patients were recruited into an ethics committee approved trial with informed consent between 2004 and 2005. All had <6 months of acute visual loss owing to subfoveal neovascular AMD and were ineligible for photodynamic therapy. METHODS: Patients underwent submacular removal of CNV through a single retinotomy. A full-thickness patch graft of RPE, Bruch's membrane, and choroid was harvested from the superior equatorial retina and transplanted into the subfoveal space. The graft was flattened under heavy liquid, before silicone oil exchange. Removal of silicone oil and cataract surgery were performed 3 months later. All patients underwent cataract grading, full refraction, optical coherence tomography, fundus autofluorescence, and fluorescein and indocyanine angiography preoperatively and again 6 months postoperatively. Retinal pigment epithelium samples from 3 patients were tested for ex vivo gene transfer using a recombinant lentiviral vector. MAIN OUTCOME MEASURES: Six months after surgery, successful transplantation was determined by the presence of a pigmented subfoveal graft showing RPE autofluorescence and choroidal reperfusion. Visual outcome was assessed by subjective refraction and microperimetry of the retina overlying the graft. RESULTS: Successful viable grafts were seen in 11 patients. Three patients had good visual function on the grafts, with mean logarithm of the minimum angle of resolution (logMAR) improving from 0.88 to 0.79 and maintained beyond 1 year. Operative complications occurred in 8 patients, including retinal detachment in 5 patients and hemorrhage affecting the graft in 4 patients. The mean visual acuity over the whole cohort fell from logMAR 0.82 to 1.16. The excised RPE choroid could also be genetically modified outside the eye with a viral vector applied within the time frame of the operation. CONCLUSIONS: Autologous RPE transplantation can in principle restore vision in neovascular AMD, but surgical complications remain high. The possibility for ex vivo gene transfer to the free graft of RPE may widen the scope of this procedure to include gene therapy or adjunctive molecular treatments for AMD.